Clinical risk factors for depressive symptoms in patients with epilepsy. (21st December 2013) - Peng, W.‐F.; Ding, J.; Li, X.; Mao, L.‐Y.; Wang, X.
<x xml:space="preserve">Abstract</x> Background and aims To investigate the relationships between demographic data, seizure‐related factors, anti‐epileptic drugs (AEDs) taking, and depressive symptoms in patients with epilepsy (PWE), determining the major clinical risk factors of depression. Methods Patients with epilepsy who visited our epilepsy clinic from 2010 to 2012 were included. The clinical data were collected, and Hamilton Depression Rating Scale (HAMD), National Hospital Seizure Severity Scale (NHS3) and Pittsburgh Sleep Quality Index (PSQI) were evaluated. Results A total of 116 PWE were recruited. They were divided into three groups. Age, duration of epilepsy, percentages of patients with partial seizures, history of status epilepticus (SE), using topiramate (TPM) or clonazepam (CZP), and using greater than or equal to 2 types of AEDs were all significantly higher in patients with moderate depressive symptoms than patients without depression. HAMD scores were positively correlated with age, duration of epilepsy, and the number of AEDs taking, respectively. PSQI scores were positively correlated with HAMD scores in patients with depressive symptoms. Age greater than 35 years, females, having partial seizures, history of SE, and using TPM were independent predictors of depressive symptoms in PWE by regression analysis. Conclusions Age greater than 35 years, females, having partial seizures, history of SE, and using TPM might become risk factors for depressive symptoms in PWE.